METHODOLOGY FOR COST FORMADON IN CONSTRUCTION - O. S. Golubova (Наука и техника)
Nowadays cost formation in construction and installation works can be carried out in accordance with methodologies which are legally prescribed for various construction sites and objects. Analysis of methodologies for cost formation in construction permits to reveal general and specific features, determine planning efficiency of work execution.